The Effect of Agricultural Supply Chain Management on the Financial Performance of Egyptian Food Industries - Thabet, Sohair (The Arab Journal of Administration, 2022)
The supply chain of agricultural products received a great deal of attention due to issues related to healthy food. This implies that the traditional supply chain practices may be subject to revision and change and the most desired change is insertion of small farmers in global value chains that often represent an opportunity for local firms and suppliers in developing countries to get access to high value markets. The paper examines the effect of agricultural supply chain management variables on the financial performance of the Egyptian food industries. The variables are working capital efficiency, asset efficiency and cost efficiency by analyzing financial statements of 12 firms from 2012 to 2020. Most of study sample’s firms are part of the public sector and very important to the Egyptian economy. The results indicate that most firms have high operational and financial risk. Moreover, cost efficiency is the most important variable that affect profitability and financial leverage of the Egyptian food industries. Agricultural supply chain should be improved by implementing a strategy to achieve cost reduction and planning the coordination of production and postharvest activities, whereas these activities are still controlled by traditional wholesales and intermediaries which are responsible for high loss.